FUN MEETS FUNCTIONALITY: EXPLORING THE ROLE OF GAMES IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOMS THROUGH THE LENS OF TEACHERS - Ahmad labib Irvani; Lulut Widyaningrum (Premise: Journal of English Education and Applied Linguistics, 2026)
How do teachers in the context of teaching English as a foreign language (EFL) with limited resources view and implement GBL after participating in targeted professional development? This study investigates how three experienced EFL teachers view GBL and the challenges they face in its implementation. Data were collected through written reflections using Gibbs' Reflective Cycle, supported by classroom observations and document reviews. Interview data were analysed using Braun and Clarke's (2006) six-phase thematic analysis. Results indicate that teachers view GBL as effective in increasing student motivation, participation, and confidence, as well as reducing anxiety about English, especially when games align with curriculum objectives and are used for clear pedagogical purposes. However, they reported structural barriers such as limited instruction time, unstable internet connections, unequal access to devices, and rigid curriculum and assessment requirements. To overcome these barriers, teachers adopted practical strategies including team-based formats, games projected to the whole class, and short, focused game activities. The study concludes that maintaining GBL in similar English as a foreign language (EFL) learning environments requires continuous professional development, adequate infrastructure, and greater curriculum flexibility.